Knowledge, attitude and practices towards zoonoses and brucellosis among medical and veterinary students in public universities in Malaysia and Nigeria - Tanko, Hamza Adamu (2016)
Introduction: Worldwide, emerging infectious diseases has continued to threaten the global health substantially. About 150 to 300 emerging infectious diseases that are transmissible between animals and humans have been identified. Interaction between man and animals increase the chance of zoonotic disease occurrence among people, their livestock, companion animals and wildlife. Brucellosis is the most common zoonotic disease and is still present throughout the five continents. In many parts of the world today brucellosis remain a disease of great economic impart and yet it is often unrecognized and frequently goes unreported. Objectives: To determine the level of knowledge, attitude and practices towards zoonoses and knowledge towards brucellosis among medical and veterinary students in Universiti Putra Malaysia and Usmanu Danfodiyo University Sokoto, Nigeria. Methodology: A cross-sectional study was conducted using a proportionate stratified sampling method among 709 eligible students from both institutions. Data was collected on knowledge, attitude and practices regarding zoonoses and knowledge towards brucellosis among students from November 2014 to April 2015, using selfadministered questionnaire, which was validated through content and face validity. Reliability was measured by checking the internal consistency using Cronbach’s alpha and values above 0.7 were considered. Descriptive analysis, Chi-square, univariate and multiple logistic regression and Mann Whitney to compare the median scores across students were conducted using SPSS version 22. Level of significance was set at P< 0.05. Result: There were a total of 709 students 369 and 340 from UPM and UDUSOK respectively. Response rate was 95.3% in UPM and 87% in UDUSOK. About 90.2% and 92.4% of the students had good knowledge in UPM and UDUSOK respectively.Majority (99.2%) in UPM and (90.6%) in UDUSOK exhibited positive attitude. However, About 71.0% and 96.2% of the students had good knowledge regarding good preventive in UPM and UDUSOK respectively. Knowledge regarding brucellosis was found to be high 97.8% in UPM and 67.1% in UDUSOK. Predictors of knowledge, attitude and practices showed that faculty predicted knowledge in UPM (ORadj = 13.241, P = 0.001*, CI = 3.928- 44.635) while year of study in UDUSOK (ORadj = 0.214, P = 0.019*, CI = 0.059-0.774). Age predicted attitude in UPM (ORadj = 63.302, P = 0.037*, CI = 1.272-3150.18), while gender and year of study in UDUSOK (ORadj = 3.451, P = 0.029*, CI = 1.136-10.48; ORadj = 4.342, P = 0.029*, CI = 1.161-16.24 respectively). Knowledge on brucellosis was predicted by faculty in UPM and UDUSOK (ORadj = 24.399, P = 0.001*, CI = 11.083-53.71; ORadj = 4.729, P =0.001*, CI = 2.149-10.40 respectively). However, year of study predicted knowledge regarding brucellosis in UDUSOK (ORadj = 0.242, P =0.001*, CI = 0.106- 0.533 respectively). Conclusion: Overall, the present study showed/demonstrated there was a high knowledge levels towards zoonoses and brucellosis. However, poor responses were established in some knowledge domains such as meaning and what zoonoses really are. Majority of the participants exhibited positive attitude towards zoonoses with better knowledge on good preventive measures.